PROSEDUR TINDAKAN BALLOON MITRAL VALVULOPLASTY PADA PASIEN MITRAL STENOSIS - Nn Ananda Rika (ARKAVI [Arsip Kardiovaskular Indonesia), 2019)
Percutaneous Balloon Mitral Valvuloplasty (BMV) was introduced in 1984 by Inoue who developed the procedure as a logical extension of surgical closed commissurotomy. Since then, BMV has emerged as the treatment of choice for severe pliable rheumatic Mitral Stenosis (MS). With increasing experience and better selection of patient, the immediate results of the procedure have improved and the rate of complications declined. When the reported complications of BMV are viewed in aggregate, complications occur at approximately the following rates: mortality (0–0.5%), cerebral accident (1–2%), mitral regurgitation (MR) requiring surgery (1.6–3%). These complication rates compare favorably to those reported after surgical commissurotomy. Several randomized trials reported similar hemodynamic results with BMV and surgical commissurotomy. Restenosis after MBV ranges from 4% to 70% depending on the patient selection, valve morphology, and duration of follow-up. Restenosis was encountered in 31% of the author's series at mean follow-up 9 ± 5.2 years (range 1.5–19 years) and the 10, 15, and 19 years restenosis-free survival rates were (78 ± 2%) (52 ± 3%) and (26 ± 4%), respectively, and were significantly higher for patients with favorable mitral morphology (MES â©½ 8) at 88 ± 2%, 67 ± 4% and 40 ± 6%), respectively (P < 0.0001). The 10, 15, and 19 years event-free survival rates were (88 ± 2%, 60 ± 4% and 28 ± 7%, respectively, and were significantly higher for patients with favorable mitral morphology (92 ± 2%, 70 ± 4% and 42 ± 7%, respectively (P < 0.0001). The effect of BMV on severe pulmonary hypertension, concomitant severe tricuspid regurgitation, left ventricular function, left atrial size, and atrial fibrillation are addressed in this review. In addition, the application of BMV in specific clinical situations such as in children, during pregnancy and for restenosis is discussed. The transseptal technique is the most common technique used to perform BMV. Keyword: Balloon Mitral Valvuloplasty